2022
DOI: 10.1007/s12072-022-10298-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-deficient transferrin is a sensitive marker of alcohol consumption in fatty liver disease

Abstract: BackgroundThe prevalence of nonalcoholic fatty liver disease (NAFLD) and alcohol-associated/related liver disease (ALD) with metabolic syndrome is globally increasing. Metabolic syndrome and excessive alcohol consumption synergically exacerbate liver pathologies; therefore, drinking-speci c serum markers unaffected by liver injury or metabolic syndrome are essential to assess alcohol consumption. We evaluated the ratio of carbohydrate-de cient transferrin to total transferrin (%CDT) in patients with fatty live… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Contrary opinion was sited by Moringa et al (2022) who reported of other parameters in LFTs such as Carbohydrate-deficient transferrin which were more sensitive than GGT 26 .…”
Section: Liver Biomarkersmentioning
confidence: 86%
“…Contrary opinion was sited by Moringa et al (2022) who reported of other parameters in LFTs such as Carbohydrate-deficient transferrin which were more sensitive than GGT 26 .…”
Section: Liver Biomarkersmentioning
confidence: 86%
“…• In controls: 1.95% (1.25-3.31) (n = 30; social drinkers consumed less than 30 g/day (210 g/week)) [20] • In non-dependents on alcohol (social drinkers): 2.2% (n = 115; alcohol non-dependents with a negative AUDIT score of ≤ 6/8 and negative diagnosis of alcohol dependence, as defined by ICD-10 and DSM-IV) [68] • Average disialotransferrin to total transferrin fraction: 1.2% (0.20) [87] • In non-drinkers: 1.71 ± 0.04%; n = 29 [88] • 6.27% (1.26-17.66) (n = 148; alcohol-dependent patients, mean alcohol consumption of 1344 g/week) [20] • 3.9% (n = 101; alcohol dependent patients with a positive AUDIT score of > 6/8 and positive diagnosis for alcohol dependence, as defined by ICD-10 and DSM-IV) [68] • Upper limit of reference interval for disialotransferrin to total transferrin fraction (in nondrinkers and light and heavy drinkers combined): 1.70% [87] • Heavy drinkers: 2.44 ± 0.14% (n = 29; consuming ≥ 420 g alcohol/week) [88] Soluble transferrin receptor (sTfR)…”
Section: Iron-related Proteins and Parameters In Serummentioning
confidence: 99%
“…For the identification of alcohol-related pathologies, CDT is mainly used in combination with other alcohol biomarkers, such as GGT and MCV [17,18]. Unlike other biomarkers, CDT is more sensitive to changes in alcohol consumption than to the secondary effects of liver disease, and it is useful to differentiate between alcoholic (ALD) and nonalcoholic fatty liver disease (NAFLD) [19].…”
Section: Introductionmentioning
confidence: 99%